1999
DOI: 10.1111/j.1472-8206.1999.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of P‐glycoprotein and intracellular metabolism in the intestinal absorption of methadone: in vitro studies using the rat everted intestinal sac

Abstract: Methadone is used as a treatment for opiate detoxification in methadone maintenance programs. Intra- and inter-patient variations in methadone bioavailability have been observed after oral methadone treatment and this makes it difficult to predict a dosing regimen. Intestinal absorption and metabolism could explain these variations. The in vitro gut sac model was used to study the intestinal absorption of methadone, and it confirmed that methadone is a substrate for P-glycoprotein. The transport of methadone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 23 publications
4
67
4
Order By: Relevance
“…Previous studies show that sinomenine is a potent inhibitor of immunity (Vieregge et al, 1999), and that its excretion is regulated by P-glycoprotein (Tsai and Wu, 2003); hence, it is possible that sinomenine can alter the disposition, absorption and bioavailability of paeoniflorin. Our preliminary experimental data using a model of rat everted intestinal sacs (Bouer et al, 1999) showed that sinomenine could act as a P-glycoprotein inhibitor, and therefore promote the intestinal transportation of drug from mucosa to serosa, this implied that the enhanced bioavailability of paeoniflorin by the co-administration of sinomenine might be closely related to P-glycoprotein (data not shown).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies show that sinomenine is a potent inhibitor of immunity (Vieregge et al, 1999), and that its excretion is regulated by P-glycoprotein (Tsai and Wu, 2003); hence, it is possible that sinomenine can alter the disposition, absorption and bioavailability of paeoniflorin. Our preliminary experimental data using a model of rat everted intestinal sacs (Bouer et al, 1999) showed that sinomenine could act as a P-glycoprotein inhibitor, and therefore promote the intestinal transportation of drug from mucosa to serosa, this implied that the enhanced bioavailability of paeoniflorin by the co-administration of sinomenine might be closely related to P-glycoprotein (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…However, the mechanism of sinomenine on enhancement of the bioavailability of paeoniflorin in rats remains unclear. There are many reports in the literature that support the hypothesis that P-glycoprotein inhibitors enhance drug absorption from the intestine, elevating the bioavailability of the drug Bouer et al, 1999). Previous studies show that sinomenine is a potent inhibitor of immunity (Vieregge et al, 1999), and that its excretion is regulated by P-glycoprotein (Tsai and Wu, 2003); hence, it is possible that sinomenine can alter the disposition, absorption and bioavailability of paeoniflorin.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo investigation utilizing knockout mice for MDR1 gene revealed higher concentrations of methadone in the brain of these animals [34] and increased analgesia [35]. In another model system, addition of verapamil to the everted rat intestine increased the transfer of methadone by 60% [36]. Accordingly, it was reasonable to assume that the unidirectional activity of P-gp could contribute to the role of the placenta as a functional barrier between maternal and fetal blood and consequently protecting the developing fetus from environmental toxins, xenobiotics, and drugs such as methadone.…”
Section: Discussionmentioning
confidence: 98%
“…Everted Sac Method According to the method of Barr and Reigelman, 11) an intestinal everted sac was prepared from drug free mice ileum to investigate whether KA has direct effect on the Rho123 uptake via P-gp. The 10 cm length of everted sac was preincubated with KA (1.0 mg/ml) at 37°C for 30 min in 50-ml glass test-tubes containing 10 ml of Krebs-Henselit buffer (pH 6.0) with supplying 95% O 2 -5% CO 2 .…”
Section: Preparation Of Standard and Test Solutionsmentioning
confidence: 99%